ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Manufaktur di BEI) Periode 2009-2011 - Yusshinta Noviana, 10.05.51.0008; Subagyo, Herry (Students Journal of Economic and Management, 2014)
This study aims to identify and analyze the influence of profitability, liquidity and solvency of the stock returns on companies listed on the Stock Exchange in the year 2009-2011. The sampled by purposive sampling method of manufacturing companies are actively traded shares on the Stock Exchange in 2009-2011. The sample in this study in 2010 and in 2011 as many as 122 as many as 118, so that the data obtained were 240 observation data. To qualify regression model testing normality, multicollinearity, autocorrelation, heteroskedasticity and regression analysis to explain the relationship between the independent variables and the dependent variable. The results obtained indicate that the data has been processed normally distributed and free from classical assumptions. The results of this study indicate that profitabilitysignificant positive effect on stock returns, liquidity no significant on stock returns. On the basis of these studies, this research suggests for subsequent research, to expand the sample, extending the years of research and add new variables. Keywords: Profitability, Liquidity, Solvency and Stock Return